Mature mediastinal teratoma with tumor rupture into airway - Jamie E. Anderson (Journal of Pediatric Surgery Case Reports, 2022)
A previously healthy 16-year-old girl presented with hemoptysis in the setting of a persistent cough for two months. Imaging identified a large mediastinal mass with cystic and solid components, calcifications and fat suggestive of a germ cell tumor. There was associated right middle lobe consolidation with an air-fluid level concerning for a necrotizing pneumonia, right upper lobe bronchiectasis, hilar lymphadenopathy, and right upper lobe and right pleural-based nodules concerning for disseminated disease. Histologic analysis of a percutaneous biopsy revealed skeletal muscle, fibroadipose tissue, skin, and keratinous debris consistent with a mature germ cell tumor. Rigid and flexible bronchoscopy were performed and identified inspissated, purulent, and fibrinous material in the right upper and middle lobe bronchi. Microbial cultures grew Staphylococcus aureus. After 3 weeks of antibiotics, complete surgical resection was performed. No malignant components were identified. Her post-operative course was uncomplicated, and she remains without evidence of disease 6 months after resection. While mediastinal teratomas are common, rupture is uncommon with fewer than 60 reported cases in the literature. Rupture can be associated with inflammation and/or infection, resulting in diagnostic and treatment challenges.